2019
DOI: 10.1002/mrm.28149
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer and frequency distribution effects in the SSFP ellipse

Abstract: Purpose: To demonstrate that quantitative magnetization transfer (qMT) parameters can be extracted from steady-state free-precession (SSFP) data with no external T 1 map or banding artifacts. Methods: SSFP images with multiple MT weightings were acquired and qMT parameters fitted with a two-stage elliptical signal model. Results: Monte Carlo simulations and data from a 3T scanner indicated that most qMT parameters could be recovered with reasonable accuracy. Systematic deviations from theory were observed in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…At the same time, in vivo estimates of relaxation parameters with CELF show biases compared to conventional spin-echo methods, due to microstructural sensitivity of bSSFP imaging. Further development of CELF is warranted to resolve these estimation errors, which might eventually provide useful opportunities for CELF in quantitative MRI applications including relaxometry, magnetization transfer (MT) mapping [43] and conductivity mapping [44].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in vivo estimates of relaxation parameters with CELF show biases compared to conventional spin-echo methods, due to microstructural sensitivity of bSSFP imaging. Further development of CELF is warranted to resolve these estimation errors, which might eventually provide useful opportunities for CELF in quantitative MRI applications including relaxometry, magnetization transfer (MT) mapping [43] and conductivity mapping [44].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Wood et al 22 has demonstrated that the PLANET method 23 , 24 , 25 for phase‐cycled bSSFP can be applied to qMT at higher field strengths to derive qMT parameter estimates free from banding artefacts. However, Wood et al 22 utilized the signal model from Gloor et al, 1 which translated into increased errors in their parameter estimation, particularly in white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Wood et al 22 has demonstrated that the PLANET method 23 , 24 , 25 for phase‐cycled bSSFP can be applied to qMT at higher field strengths to derive qMT parameter estimates free from banding artefacts. However, Wood et al 22 utilized the signal model from Gloor et al, 1 which translated into increased errors in their parameter estimation, particularly in white matter. We hypothesize that combining the method from Wood et al 22 with our methods here would provide increased accuracy, leading to a method which can produce qMT parameter estimates quickly over all clinical field strengths.…”
Section: Discussionmentioning
confidence: 99%
“…CELF shows improved estimation accuracy compared to PLANET, and it offers higher scan efficiency by reducing the number of required. This scan efficiency can provide useful opportunities in other quantitative applications such as magnetization transfer (MT) parameter mapping [43], and conductivity mapping [44].…”
Section: Discussionmentioning
confidence: 99%